Agricultora no cuidado da família com uso das plantas medicinais - Lima, Ângela Roberta Alves (2012)
Farm women usually have knowledge on medicinal plants and most recurrent pathologies in their region and use it in care within the family structure and the community. This research aimed to investigate the context faced by farm women in relation to family care with the use of medicinal plants. Methodology consists of an exploratory, descriptive and qualitative study, conducted with a group of farm women, with a total of fifteen informants, residents in the rural area of Pelotas. Data collection occurred from August to October, 2011 and from March to July, 2012. Participant observation, focus groups and individual interviews were used as instruments of data collection. Data were analyzed and grouped into three themes: the ethnobotanical survey of medicinal plants used in homemade preparations. the contextualization of farm women; and care actions with use of medicinal plants. Eighty medicinal plants, eight elixirs, two syrups and six creams were mentioned. Medicinal plants are seen as a resource for female domain that are present in the environment in face of situations of greater or lesser severity. They are considered as the best health resource because they have fewer side effects and lower cost. It was observed that medicinal plants and preparations based in them have an important role in rural families care and can positively contribute to the restoration and/or prevention of various problems acting mostly as a complementary form to allopathy. In respect to nursing, it is important to recognize that care actions performed by farm women in their household based on the use of medicinal plants tend to be effective and allow their families have better health conditions.